2021
DOI: 10.1186/s40478-021-01160-3
|View full text |Cite
|
Sign up to set email alerts
|

SCF + G-CSF treatment in the chronic phase of severe TBI enhances axonal sprouting in the spinal cord and synaptic pruning in the hippocampus

Abstract: Traumatic brain injury (TBI) is a major cause of long-term disability in young adults. An evidence-based treatment for TBI recovery, especially in the chronic phase, is not yet available. Using a severe TBI mouse model, we demonstrate that the neurorestorative efficacy of repeated treatments with stem cell factor (SCF) and granulocyte colony-stimulating factor (G-CSF) (SCF + G-CSF) in the chronic phase is superior to SCF + G-CSF single treatment. SCF + G-CSF treatment initiated at 3 months post-TBI enhances co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 86 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…For example, a mild controlled cortical impact induced an increase in filopodia spines [ 38 ], and a moderate impact caused a decrease in filopodia and no alterations in the number of stubby spines [ 26 ]. With a more severe controlled cortical impact, mushroom and stubby spines diminished, and the filopodia number remained unchanged [ 39 ]. Hence, our results show that Shank3 deficiency abrogates the effects of mTBI observed in WT animals.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a mild controlled cortical impact induced an increase in filopodia spines [ 38 ], and a moderate impact caused a decrease in filopodia and no alterations in the number of stubby spines [ 26 ]. With a more severe controlled cortical impact, mushroom and stubby spines diminished, and the filopodia number remained unchanged [ 39 ]. Hence, our results show that Shank3 deficiency abrogates the effects of mTBI observed in WT animals.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that G-CSF can enhance neurological function by promoting the sprouting of the corticospinal tract into the denervated side of the cervical spinal cord. Additionally, G-CSF may mitigate microglia degeneration and restore a proper balance in synaptic pruning within the hippocampus, leading to improved neurological outcomes [65]. Similarly, studies have shown that GM-CSF may also have significant protective properties in the chronic consequences of experimental TBI [66,67].…”
Section: Swcnt-peg Modulate the Secretory Function Of Astrocytes Expo...mentioning
confidence: 99%